Comprehensively Summarizing What Distracts Students from Online Learning: A Literature Review - Chenghao Wang (Human Behavior and Emerging Technologies)
As online learning becomes an indispensable component of the current education system, students benefit from the advantages of online education. At the same time, students are also facing more challenges during online learning. Multitasking, mind-wandering, and using digital devices are the extensively discussed types of distractions that detriment students’ learning performance by impairing their focused attention. However, the consensus on the definition of distraction and what represents distraction during online learning are still lacking. This literature review develops a comprehensive definition of distraction, summarizes three main types of distraction (multitasking, mind-wandering, and using digital devices), and proposes two new types of distraction (unexpected interruption and consistent interference). Since the detrimental effects of distraction on online learning are salient, more explorations on helping students to resist distractions and maintain focused attention are imperative for future studies.